Barriers to healthy eating in Switzerland: A nationwide study. Issue 6 (December 2016) - de Mestral, Carlos; Stringhini, Silvia; Marques-Vidal, Pedro
Summary: Background & aims: Several barriers can hinder healthy eating in the population. We aimed to assess the prevalence of self-reported barriers to healthy eating in Switzerland and examine their socioeconomic and demographic determinants. Methods: Using representative cross-sectional data from the Swiss Health Survey 2012, we assessed, separately by gender, the prevalence of ten barriers and their association with demographic and socioeconomic determinants; we used age- and multivariable-adjusted logistic regression and report the odds ratio for likelihood to identify each barrier according to each demographic and socioeconomic determinant. Results: The most prevalent barriers were "price" (43.2% in women, 35.8% in men), "daily habits, constraints" (39.8%, 37.5%), "fondness of good food" (38.8%, 51.0%), "time constraint" (34.8%, 29.0%) and "lack of willpower" (22.0%, 21.2%). Prevalence of most barriers decreased with age, increased for "fondness of good food" and remained constant for "price." After multivariable adjustment, obese participants were more likely to report "fondness of good food" [Odds ratio (95% confidence interval) for obese vs. normal weight women and men, respectively: 1.63 (1.38–1.91), 2.02 (1.72–2.38)]. Participants with lower education were more likely to report "fondness of good food" [mandatory vs. tertiary women and men, respectively: 1.93 (1.62–2.39), 1.51 (1.26–1.81)], but less likely to report "lack of willpower" [0.45 (0.38–0.55), 0.40 (0.33–0.49)] and "time constraint" [0.61 (0.51–0.73), 0.78 (0.63–0.96)]. Participants with lower income were more likely to report "price" [lowest vs. highest quartile for women and men, respectively, 1.65 (1.43–1.90), 1.47 (1.26–1.71)] but less likely to report "lack of willpower" [0.71 (0.61–0.82), 0.40 (0.33–0.49)]. Smoking, living situation, nationality and living area showed little or no association. Conclusion: Several barriers to healthy eating were highly prevalent regardless of gender; the most important determinants were age, obesity, education, and income, with different effects per barrier. This requires multifaceted interventions to tackle several barriers simultaneously.